Fever Duration, Hepatomegaly And Overweight With The Dengue Shock Syndrome In Kupang, East Nusa Tenggara - Cundawan, Robertus S; Wihanto, Laura; Wijono, Steven (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Dengue infection is an infection caused by the dengue virus. Community-widespread cases of morbidity and mortality are often found in Extraordinary Events (KLB)in Indonesia, especially in children. Purpose: The purpose of this study was to prove the correlation between the duration of fever, hepatomegaly, and overweight with dengue shock syndrome in Kupang, East Nusa Tenggara. Methods: This research is an observational analytic study with a case-control approach—the subject in this study was data of dengue infection patients aged 5-14 years. The research instrument used was the patient's medical record data for the period June 2018-June 2019. Bivariate analysis was done using chi-square statistical test. Results: The results showed that there was a significant correlation (p<0.05) between the duration of fever (OR=0,35;p=0,04), hepatomegaly (OR=3,34;p=0,022), and overweight (OR=2,88;p=0,033) with dengue shock syndrome in Kupang, East Nusa Tenggara. Conclusion: There is a significant relationship between the duration of fever, hepatomegaly, overweight with dengue shock syndrome.